Genome-Wide Identification of Wild Soybean Mitochondrial Calcium Uniporter Family Genes and Their Responses to Cold and Carbonate Alkaline Stresses - Li, Jianwei; Sun, Mingzhe; Liu, Yu; Sun, Xiaoli; Yin, Kuide (Frontiers in Plant Science, 2022)
MCU (mitochondrial calcium uniporter), as an important part of Ca2+ channel uniporter complex, plays a regulatory role in intracellular Ca2+ signal transduction. However, up to now, few studies have been reported about plant MCU genes. In this study, we genome-widely identified the MCU family in wild soybean, and investigated their expression under cold and carbonate alkaline stresses. A total of eleven Glycine soja MCU genes (GsMCUs) were identified. Phylogenetic analysis showed that GsMCUs were clustered into two subgroups (subgroup I and subgroup II), and subgroup II could be further divided into two branches (MCU5 and MCU6). A total of 21 duplicated pairs were found among 11 GsMCUs, and duplicated pairs displayed similar exon-intron architecture. All GsMCU proteins contained one conserved MCU domain, within which two transmembrane domains were found. Furthermore, analysis of conserved motifs further supported that GsMCUs showed high conservation in protein sequence and structure. Moreover, we found that all GsMCUs were expressed ubiquitously in different tissues and organs, and GsMCUs from the same subgroup displayed varied tissue expression profiles. In addition, based on RNA-seq and qRT-PCR assays, six and nine GsMCUs were differentially expressed under cold and carbonate alkaline stresses, respectively. Promoter analysis also uncovered the existence of two canonical cold-related cis-acting elements LTR and DRE/CRT, as well as stress-related phytohormone responsive elements. Our results provide valuable information on the soybean MCU family in plant responses to cold stress, which will be helpful for further characterizing their biological roles in responding to cold stress.